2009
DOI: 10.1007/s00198-009-1026-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of fracture: evaluation of predictive accuracy of the FRAX™ algorithm and Garvan nomogram

Abstract: In this analysis, although both approaches were reasonably accurate in women, FRAX discriminated fracture risk poorly in men. These data support the concept that all algorithms need external validation before clinical implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 26 publications
1
83
1
2
Order By: Relevance
“…Noteworthy, other investigators reported the lack of sensitivity of FRAX in elderly women (27)(28)(29) and in some male populations. (30) We found that parity, which is not included in the FRAX algorithm, was a significant predictor of the risk of major OP fracture, independent of BMD and of the other CRFs. This risk factor may be more important with regard to fracture risk prediction in early postmenopausal women than in older women.…”
Section: Discussionmentioning
confidence: 67%
“…Noteworthy, other investigators reported the lack of sensitivity of FRAX in elderly women (27)(28)(29) and in some male populations. (30) We found that parity, which is not included in the FRAX algorithm, was a significant predictor of the risk of major OP fracture, independent of BMD and of the other CRFs. This risk factor may be more important with regard to fracture risk prediction in early postmenopausal women than in older women.…”
Section: Discussionmentioning
confidence: 67%
“…In a study from an independent cohort of Australian men and women, assessing the ability of the Garvan model (including age, sex, prior fractures, falls, and either femoral neck BMD or body weight) and the FRAX algorithm to predict OP fracture, the authors found that the Garvan model had good discriminatory performance for fracture prediction in both men and women, whereas discriminatory performances of the FRAX was better in women than in men. (27) In addition, even if the number of hip fracture during follow-up was of the same order as the probability given by the calculation of FRAX, it was too low to permit further interpretable analysis. Finally, some differences between predicted probability and observed incidence of major OP fractures may become significant with a bigger sample size.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Garvan underestimates fracture risk in women with a parent history of hip fracture and in women with secondary osteoporosis. In spite of these differences, both approaches were reasonably accurate in women [Sandhu et al 2009].…”
Section: Therapeutic Advances In Musculoskeletal Disease 2 (2)mentioning
confidence: 91%
“…In the Women's Health Initiative (WHI) study, 11 factors predicted hip fracture within 5 years, of which two were related to fall risk (self-reported health and self-reported physical activity), independent of age, weight, height, race/ethnicity, history of fracture after age 54 years, parental hip fracture, current smoking, current corticosteroid use, and treated diabetes [Sandhu et al 2009].…”
Section: Therapeutic Advances In Musculoskeletal Disease 2 (2)mentioning
confidence: 99%